Implementation of Building Information Modeling (BIM) on Drainage Channel Design in UB Forest Sumberwangi Area - Rika Rosita Sari; Dermawan , Very; Cahya , Evi Nur (Fakultas Teknik, Universitas Brawijaya, 2023)
Road damage in the UB Forest Sumberwangi Area, Karangploso District, Malang Regency, is one of the harmful impacts of the drainage system. This study aims to analyze an accurate and efficient drainage system by applying modern methods, namely Building Information Modeling (BIM). By using BIM, the analysis of drainage work becomes faster and more accessible than with conventional methods. BIM is beneficial in building and analyzing drainage network data quickly and effectively and can help expand it to provide more accurate results. BIM can integrate models based on technical data and simulate development information into a three-dimensional model. BIM is used to perform 3D modeling of drainage channels using Autodesk Civil 3D, as well as analyzing channels from both hydrology and hydraulics with Storm and Sanitary Analysis (SSA). After calculating the design for a 5-year return period rainfall, channel dimensions of 50 x 50 cm and 30 x 30 cm were obtained. Based on the hydraulic analysis, it is known that several points have velocities that exceed the maximum velocity for the concrete surface (v < 3 m/s), so it is necessary to build a drop structure with h = 1 m. The quantity take off and the volume are calculated by Civil 3D for cut and fill work 7824.07 m3 and 1389.79 m3, respectively.